Large-scale integrated infrastructure for asynchronous microservices architecture - Ramadhan, Insan; Guarddin, Gladhi (Jurnal Teknologi dan Sistem Komputer, 2022)
Integrated large-scale business activities increasingly rely on the use of remote resources and services across multi-platform applications. Microservice in previous research has become a solution, but this approach still leaves a data loss problem. This research methodology proposed an architecture of data transmission managed by messaging service to prevent data loss in handling many requests to deliver a multiplatform architecture, handling the plugin services, and enabling escalation based on the requirement. As a result, this research successfully implements large-scale multiplatform Single Sign-On (SSO) infrastructure for asynchronous microservices architecture. The system test results show that the developed system can handle up to 2000 requests with 20 concurrent requests.